Probleme und Perspektiven des Schulfaches. ,Arbeitslehre" in Deutschland - Dedering, Heinz (Wydawnictwo Naukowe UAM w Poznaniu, 1992)
The book discussses some issues concerned with teaching of working as a component of overall education. The author refers the past educational practice in the field to different aspects of the dynamics of the social-labor world, and indicates deep incohesion of the present reality of work-teaching and new functions and goals of the educational field which are derived from the present and future changes in labor world and the place of labor in human life activities. This is the author's perspective to build a thesis for defining ways of change in the doctrine of work-teaching.
Problems and perspectives of the subject „work-teaching" in Germany
Keywords: Praca nauczyciela; Work-teaching; Problemy edukacji; Problems of education; Szkoła; School; Edukacja; Education; Oświata; Learning